2005
DOI: 10.1590/s1519-566x2005000100005
|View full text |Cite
|
Sign up to set email alerts
|

Análise quantitativa e distribuição de populações de espécies de Anastrepha (Diptera: Tephritidae) no campus Luiz de Queiroz, Piracicaba, SP

Abstract: -The distribution of females of Anastrepha species per trap was strongly clustered, with five traps (6%) capturing 50% of the total of females. Only Anastrepha fraterculus (Wied.) and A. obliqua (Macquart) were dominant species. A. fraterculus was by far the most frequent species (80.2% of the females), and the most constant, occurring in 98.0% of the samples. In decreasing order of frequency, A. obliqua (12.6%), A. pseudoparallela (Loew) (3.1%), and A. bistrigata Bezzi (2.1%) comprised the other major species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 11 publications
2
23
1
22
Order By: Relevance
“…The highest percentage of capture of A. fraterculus is here related to the fact of its poliphagous behavior and the existence of many species of Myrtaceae (its preferred host) in sampled areas. Others studies in this region also showed the dominance of this species (Bittencourt et al, 2006a;Dutra et al, 2009;Santos et al, 2008;Santos et al, 2011) and in others regions of Brazil (Araújo et al, 2013;Uramoto et al, 2004Uramoto et al, , 2005.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The highest percentage of capture of A. fraterculus is here related to the fact of its poliphagous behavior and the existence of many species of Myrtaceae (its preferred host) in sampled areas. Others studies in this region also showed the dominance of this species (Bittencourt et al, 2006a;Dutra et al, 2009;Santos et al, 2008;Santos et al, 2011) and in others regions of Brazil (Araújo et al, 2013;Uramoto et al, 2004Uramoto et al, , 2005.…”
Section: Resultsmentioning
confidence: 55%
“…Each species of Anastrepha were ranked according to the indexes of Shannon-Wiener, Margalef and equitability, and categorized according to its dominance (SD = super-dominant, D = dominant, and ND = not dominant), abundance (sa = superabundant, va = very abundant, c = common, d = disperse), frequency (SF = super-frequent, VF = very frequent, F = frequent, and LF = low frequent) and constancy (W = constant, Y = accessory, Z = incidental) in the community (Silveira Neto et al, 1976;Zucchi, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species were considered dominant if their relative abundance was higher than 1/S, where S = species richness (Uramoto et al, 2005). We calculated the Jackknife1 species richness and plotted the cumulative species curves (observed and estimated) based on 1000 iterations (see Colwell and Coddington, 1994) in EstimateS 8.0 (Colwell, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…O baixo valor encontrado tanto para o índice de diversidade (H') quanto para o índice de equitabilidade (E) pode estar relacionado ao reduzido número de plantas hospedeiras dos tefritídeos, principalmente relacionada a espécies frutíferas (FERRARA et al, 2005;URAMOTO et al, 2005), em que a produção diversificada de frutíferas e cultura de subsistência contribuíram de maneira primordial para a diversidade de espécies de moscas-das-frutas.…”
Section: Resultado E Discussãounclassified